Effect of Anticoagulant on Acetylsalicylic Acid and Salicylic Acid Analysis in Plasma In Vitro with High Performance Liquid Chromatography - Yahdiana Harahap (Journal of Global Pharma Technology, 2019)
Background: Evaluation of the anticoagulant effect and analysis of acetylsalicylic acid (ASA) and salicylic acid (SA) is important. Full validation of in vitro methods using citrate anticoagulant in the form of CPD-A has previously been done, whereas in the implementation of in vivo studies, EDTA and heparin were used as anticoagulants. Based on EMEA 2011, if there are anticoagulant changes in validated analysis methods then partial validation should be performed. Objective: This study aims to evaluate the effect of different types of anticoagulants on the analysis of ASA and SA in plasma after being preceded by partial validation. Materials and Method: Analysis was performed using high pressure liquid chromatography column C18 (Waters, ReliantTM 5μm; 250 x 4.6 mm); mobile phase acetonitrile - phosphate buffer 20 mM (35:65) with pH 2.5; 1.0 mL/min flow rate; column temperature 35˚C; 14 minutes of time analysis with furosemide as internal standard. Results: Accuracy and precision in plasma citrate, heparin, and EDTA analysis fulfilled linear calibration curves in ASA and SA. Stability and recovery of ASA and SA in plasma with different anticoagulants showed no significant difference, however the peak area response ratio for the three types of anticoagulants between plasma with anticoagulant heparin-citrate and EDTA-citrate showed significant difference and plasma with heparin anticoagulant provides a larger area than plasma with EDTA anticoagulants. Conclusion: From this experiment, the analytical methods obtained were considered to meet the validation requirements for use of citrate, heparin, or EDTA anticoagulants based on EMEA 2011.